Sol-gel coatings incorporating borosilicate bioactive glass enhance anti corrosive and surface performance of stainless steel implants - Balestriere, M. A.; Schuhladen, Katharina; Herrera Seitz, K.; Boccaccini, Aldo R.; Cere, S. M.; Ballarre, J. (Journal of Electroanalytical Chemistry, 2020)
Metals are the most used materials as orthopaedic or dental implants due to their excellent mechanical properties. Stainless steel is one of the most commonly used materials based on its excellent mechanical properties and low costs compared with other metals, e.g. titanium alloys. In developing countries it is still one of the most used materials for temporary devices like bone plates and fixation screws and for permanent orthopaedic implants. However, stainless steel does not have good anticorrosive and bioactive surface properties in physiological media in comparison to other metals: stainless steel is not able to create a natural bonding with bone and might release corrosion products that could finally end in the removal of the implant. A promising approach to avoid those effects is to protect the implant with a functional coating, which additionally may have antibacterial properties. In this work, three kinds of bioactive glass particles (silicate, borosilicate and copper-doped borosilicate) were added as a second phase to a hybrid organic-inorganic silica based sol-gel made coating, with the aim of improving the surface properties of stainless steel as implant material. Chemical composition of the particles and coatings as well as the bioactive and anti-corrosive behaviour of the generated coating systems were analysed by Fourier Transformed Infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and by electrochemical tests. After 14 days of immersion in simulated body fluid solution, the particles contained in the coatings presented a slow dissolution, generating phosphate-rich deposits (first insight of bioactivity) and enhancing the electrochemical response.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Bioactivity; Corrosion protection; Cu-borosilicate bioactive glass; Sol-gel; Stainless steel